Abundance and Diversity of Sponges in the Waters of Pasumpahan Island, West Sumatra - Rusdi, Muhammad; Efriyeldi, Efriyeldi; Thamrin, Thamrin (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2025)
Sponges are the most primitive multicellular animals that live in various types of waters, ranging from fresh to brackish and marine. Sponges live at the bottom of the water, usually embedding themselves in rigid substrates such as rocks or corals and competing with other attached organisms for food space. This study aimed to analyse the abundance and diversity and determine the differences in sponge abundance at different depths. This research was conducted in March 2024 in Pasumpahan Island, West Sumatra. This research used the survey method and the belt transect method. The sampling location was divided into three stations consisting of 3 sampling points. Station I is located in the tourist area, Station II is in the dock area, and Station III is in the area facing the open sea. The results showed that the highest abundance based on depth was found at station I with a depth of 5 m, namely 1071.4 ind / ha and the lowest abundance at station II with a depth of 7 m, 714.286 ind / ha. The t-test results obtained a significant value of less than 0.05, namely 0.048, which means that the abundance of sponges at different depths is significantly different. The diversity index ranges from 1.930 to 2.013, indicating that the sponge diversity level in Pasumpahan Island waters is classified as moderate. The T-test results show a significant value of more than 0.05, namely 0.795, which means the abundance of sponges at two depths is significantly different